2016
DOI: 10.1002/adsc.201500930
|View full text |Cite
|
Sign up to set email alerts
|

Improved Second Generation Iron Pincer Complexes for Effective Ester Hydrogenation

Abstract: Hydrogenation of esterst oa lcoholsw ith aw ell-definedi ron iPr2 PNP pincerc omplexh as been recently reported by us and other groups.W en ow introduce an ovel and sterically less hindered Et2 PNP congener that provides superior catalytic activity in the hydrogenation of various carboxylic acid esters and lactones comparedt ot he known complex. Successful hydrogenation proceeds under relatively mild conditions (60 8 8C) with lower catalyst loadings.Keywords: alcohols;c atalytic hydrogenation;esters; iron;p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 60 publications
1
51
0
Order By: Relevance
“…[11] The groups of Schneider, [11g] Guan, [12] and Beller [13] independently reportedt he synthesis of iron compound A (Scheme 2), which is an effective catalyst for the hydrogenation of esters, [12][13][14] nitriles, [15] and heterocycles. [11] The groups of Schneider, [11g] Guan, [12] and Beller [13] independently reportedt he synthesis of iron compound A (Scheme 2), which is an effective catalyst for the hydrogenation of esters, [12][13][14] nitriles, [15] and heterocycles.…”
Section: Resultsmentioning
confidence: 99%
“…[11] The groups of Schneider, [11g] Guan, [12] and Beller [13] independently reportedt he synthesis of iron compound A (Scheme 2), which is an effective catalyst for the hydrogenation of esters, [12][13][14] nitriles, [15] and heterocycles. [11] The groups of Schneider, [11g] Guan, [12] and Beller [13] independently reportedt he synthesis of iron compound A (Scheme 2), which is an effective catalyst for the hydrogenation of esters, [12][13][14] nitriles, [15] and heterocycles.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Whereas in recent years,m ajor developments have been achieved with iron and cobalt complexes both for hydrogenation and dehydrogenation reactions,m anganese is much less explored. [11] Since then, an improved secondgeneration iron pincer complex [12] and different cobalt com-plexes [13] have been published for effective ester hydrogenation. [10] Furthermore,o ur group and Guan and co-workers independently described hydrogenation reactions of non-activated esters with PNP iron pincer complexes.…”
mentioning
confidence: 99%
“…During our studies on the catalytic behavior of aliphatic iron, or manganese pincer complexes we observed the beneficial effect of carbonyl ligands that are coordinated to the metal centre. Therefore, we tested various, carbon monoxide‐containing cobalt pincer species 5 , 6 and 8 in this model reaction.…”
Section: Figurementioning
confidence: 90%
“…So far, all these cobalt catalysts have been tested for a relatively small number of esters with a limited tolerance of functional groups leaving space for improvements. Here, based on our experiences in non‐noble‐metal‐catalyzed reductions, we report the development of a more general applicable cobalt catalyst for the hydrogenation of various carboxylic acid esters.…”
Section: Figurementioning
confidence: 99%